Hepatitis C virus infection in a large cohort of homosexually active men: independent associations with HIV-1 infection and injecting drug use but not sexual behaviour. Issue 2 (April 1996) - Bodsworth, N J; Cunningham, P; Kaldor, J; Donovan, B
Abstract : OBJECTIVE: To determine the prevalence and risk factors for hepatitis C virus (HCV) infection in a cohort of homosexually active men, with particular reference to assessing sexual transmission. DESIGN: Prevalence based on cross-sectional testing for HCV (c100 protein) antibody in a cohort using sera stored between 1984 and 1989, and assessment of risk factors using a case-control analysis based on questionnaire data from HCV positive and negative subjects. SUBJECTS/SETTING: 1038 homosexually active men who were participating in a prospective study established to identify risk factors for AIDS. They had been recruited through private and public primary care and sexually transmissible disease (STD) services in central Sydney. MAIN OUTCOME MEASURES: Prevalence of HCV antibody and its association with human immunodeficiency virus type 1 (HIV-1) infection and other STDs, number of sexual partners, sexual practices and recreational drug use. RESULTS: Overall, 7.6% of subjects tested were seropositive for HCV antibody. In univariate analysis, HCV infection was significantly associated with injecting drug use (IDU) (OR = 8.18, p < 0.0001) and HIV infection (OR = 3.14, p < 0.0001) and with self reported history of syphilis (OR = 1.88, p = 0.016), anogenital herpes (OR = 1.93, p = 0.017), gonorrhoea (OR = 2.43, p = 0.009) and hepatitis B (OR = 1.92, p = 0.010). In case control analysis, similar sexual behaviours (partner numbers and practices) were reported by HCV positive and HCV negative subjects except that HCV negative subjects more frequently reported engaging than HCV positive subject in unprotected receptive anal intercourse without ejaculation (OR = 0.61, p = 0.034), unprotected insertive (OR = 0.59, p = 0.039) and receptive (OR = 0.56, p = 0.016) oro-anal intercourse (rimming) and insertive fisting (OR = 0.48, p = 0.034). In multiple logistic regression analyses, only HIV-1 infection (OR = 3.18, p < 0.0001) and IDU in the previous six months (OR = 7.24, p < 0.0001) remained significantly associated with the presence of HCV antibody. CONCLUSIONS: IDU was the major behavioural risk factor for HCV infection. If sexual or another from of transmission did occur, it may have been facilitated by concurrent HIV-1 infection.